Japanese language education students' ability to identify the meaning of the sentence ending particle janai - Ainurrafik, Shifa Fikriyya; Febriyanti, Rike (Japanese Research on Linguistics, Literature, and Culture, 2024)
This study aims to determine the ability of students, especially Japanese Language Education Study Program students at Universitas Brawijaya, to identify the meaning of the sentence ending particle janai in the context of sentences pronounced by native Japanese speakers. This study used a descriptive qualitative method. The instrument used to obtain data is a question in the form of a questionnaire then followed by an interview. The results obtained based on all meaning identification data and interviews, respondents were able to understand the meaning of the final particle janai meaning confirmation in theory and context compared to the meaning of the final particle janai meaning others. This is because the duration of learning these final particles is not balanced, so respondents still find it difficult to understand the context of the sentence.